2009
DOI: 10.1111/j.1365-2265.2008.03476.x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E and Paraoxonase 1 polymorphisms are associated with lower serum thyroid hormones in postmenopausal women

Abstract: Polymorphisms of apolipoprotein E and paraoxonase 1 are associated with different levels of thyroid hormone and anti-Tg antibody levels in the study population in this pilot study. The mechanism underlying this association remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…It should be noted that only a few studies concerning the impact of the APOE gene polymorphism on thyroid status are available in the literature. Our findings are in agreement with those of Lambrinoudaki et al [41] that also demonstrated lower levels of thyroid hormones in postmenopausal healthy women with a ε4 allele. So far, no pathophysiological mechanism responsible for this state has been established.…”
Section: Discussionsupporting
confidence: 83%
“…It should be noted that only a few studies concerning the impact of the APOE gene polymorphism on thyroid status are available in the literature. Our findings are in agreement with those of Lambrinoudaki et al [41] that also demonstrated lower levels of thyroid hormones in postmenopausal healthy women with a ε4 allele. So far, no pathophysiological mechanism responsible for this state has been established.…”
Section: Discussionsupporting
confidence: 83%
“…A study performed on healthy post-menopausal women with no pesticide exposure found a negative association between R allele of the polymorphism PON1 192 and free T3 levels [13]. Additionally, in male flower workers from a floricultural area of Mexico, our research group found a positive association between urine concentration of dialkylphosphate (DAP) OP metabolites and TSH and total T4 levels and a negative association with total T3 [6], as well as a decrease in the percentage of variation of TSH among carriers of PON1 192 RR genotype [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, researchers have reported their attempts to combine genetic variants with different aspects of menopausal syndromes [ 3 , 5 , 6 , 32 ]. We selected two genes in our study: one for APOE and one for LEP , on the basis of biological conditions mentioned in [ 33 , 34 , 35 , 36 , 37 , 38 ] to be associated with menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the “other genotypes” group might not show this significant difference because the sample size of this group is smaller. Furthermore, Lambrinoudaki et al [ 35 ] observed in their pilot study that polymorphisms of APOE and paraoxonase 1 are associated with different levels of the thyroid hormone and anti-TG antibody levels in the study population. A statistically significant correlation was found between apolipoprotein E polymorphisms and serum thyroid hormones: carriers of the E2 or E4 allele of the APOE gene had lower levels of FT4 than women with the E3E3 genotype.…”
Section: Discussionmentioning
confidence: 99%